Guernsey trust law - Pursall, Tony; Guthrie, Matthew (Lawyer) (Oxford [England] : Hart, 2020)
"This book is intended to be a comprehensive treatise of Guernsey trust law providing answers for practitioners advising on Guernsey trusts and trustees administering them. In particular, it provides a detailed analysis of the provisions of the Trusts (Guernsey) Law 2007 (as amended), a consideration of Guernsey trust cases as well as relevant cases in Jersey and in other jurisdictions, and analysis of the legal principles underpinning Guernsey trust law. Where there is no clear Guernsey authority on a particular point of law it gives a reasoned view, drawing on relevant legal principles, together with a broad assessment of the confidence of which the authors hold that view"--
Foundation and Principles -- Express Trusts -- Trusts Arising by Operation of Law -- Taxation -- Creation, Validity and Termination -- Conflict of Laws -- Trustees -- Powers, Duties and Liabilities of Trustees -- Beneficiaries -- Protectors -- Trust Investments -- Introduction to Trust Litigation -- Attacks on Trusts -- Variation of Trusts -- Remedial Applications to Court -- Regulation of Fiduciaries -- The Public Trustee.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Trusts and trustees -- Guernsey; Equity & trusts; Electronic books